Appassionata para violão solo de Ronaldo Miranda: o tratamento octatônico e as constâncias musicais brasileiras - VIEIRA, Márlou Peruzzolo (2010)
This research discusses some constitutive elements of the Appassionata for solo guitar written by Ronaldo Miranda. Characteristics concerning the Appassionata's two themes are analyzed pointing out the techiqnues of the twentieth century music in oppostion to Brazilian music features. Regarding the first theme, it is discussed aspects of the octatonic treatment, verifying the insertion of melodic and harmonic resources derived from the otctatonic scale in the context of neotonal language. About the second theme, it is discussed aspects related to the Brazilian musical constancies through the analysis of harmonic, polyphonic, rhythmic and melodic structures.